Critical Analysis of Indonesia's Global Maritime Fulcrum under Joko Widodo: Problems and Challenges - Alfiyan Nooryan Putra Pikoli (Universitas Muhammadiyah Gorontalo, 2021)
The vision of the Global Maritime Fulcrum (GMF) for Indonesia not only raises national awareness but also gets international attention. Jokowi in the first term of his administration echoed this vision as the identity of his foreign policy. However, in its implementation, there are various shortcomings. As a result, the vision did not work out well. Especially during his second election as president of Indonesia, Jokowi no longer mentioned GMF as a priority policy. This paper aims to analyze the causes of the failure to implement the GMF vision in Jokowi's first term as president. Several previous studies on GMF were divided into 3 major studies, namely security studies, international cooperation, then regional and geopolitical studies. Most of these studies discuss GMF Indonesia's vision only in the international scope, such as cooperation formed with other countries, its influence on the region, geopolitical implications, and also on the perspective of threats and security. There is no research that specifically addresses the problems and challenges of the GMF. By the governmental and leadership approach in policy studies, this paper identifies the factors that have resulted in the GMF vision's lack of implementation. This article argues that uncoordinated governance, overlapping institutions, and Jokowi's lack of leadership are the main determinants of the success or failure of the GMF vision. The limitations of this study allow for further analysis of the economic perspective of GMF in subsequent studies.